HUBUNGAN PENYAJIAN SUSU FORMULA DENGAN KEJADIAN DIARE PADA BAYI USIA 6 -12 BULAN DI PUSKESMAS LUBUK BAJA KOTA BATAM - Sarita Miguna; Isramilda; Elvita Nora Susana; Amanda Putri (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Diarrhea is one of the leading causes of morbidity and mortality in infants in Indonesia. One contributing factor to the incidence of diarrhea is the improper preparation of formula milk that does not adhere to hygiene and sanitation standards. Infants who do not receive exclusive breastfeeding are more susceptible to gastrointestinal infections, including diarrhea. This study aims to analyze the relationship between formula milk preparation and the incidence of diarrhea in infants aged 6-12 months at Lubuk Baja Public Health Center, Batam City. Methods: This study employed an analytical survey design with a cross-sectional approach. The sample consisted of 40 mothers with infants aged 6-12 months who consume formula milk, selected using a total sampling method. Data were collected through questionnaires and maternal and child health (MCH) book records, then analyzed using the chi-square test to determine the relationship between formula milk preparation and the incidence of diarrhea. Results: The study results indicated that most infants who experienced diarrhea were associated with poor formula milk preparation practices. The chi-square test showed a significant relationship between formula milk preparation and the incidence of diarrhea in infants (p = 0.002). Conclusion: Improper formula milk preparation that does not meet hygiene standards is associated with an increased risk of diarrhea in infants aged 6-12 months Keywords: Diarrhea, Formula Milk, Baby